SPIRITUALITAS DITENGAH TANTANGAN MODERN - Frans, Imanuella R (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2023)
Abstract:The importance of religion for individuals shows a positive correlation with feelings of depression (personal distress), belief in the existence of God has a curvelinear relationship with feelings of depression (personal distress). And feeling meaningful has a negative correlation with feeling depressed. Other religiosity and spirituality variables did not correlate with feelings of depression (dependence on great powers, belief in life after death, belief in heaven and hell, visits to places of worship, frequency of prayer, rebirth as a Christian, and current religious choice). . Modernism is seen as a "movement" of thought at a certain phase in the development of human history to handle the "project" of developing civilization and humanity, appearing in several themes. The separation between the sacred and the worldly, which in practical life is reflected in the separation between religion and state, religion and politics, is precisely called secularism.Key words: Spirituality; Religion; Modern.